Anthracycline-induced cardiomyopathy. Issue 883 (1st May 1999) - Fisher, N G; Marshall, A J
Abstract : Anthracycline cardiomyopathy is less frequently encountered nowadays, due to the well-recognised dose limitations and cardiac monitoring protocols used by chemotherapy centres. However, it is a condition that will persist due to the sensitivity of some patients to these drugs and the necessity for large doses to be used for certain individuals. We have demonstrated the benefit of angiotensin-converting enzyme inhibitor therapy and would consider introducing these compounds at the earliest opportunity. The use of probucol and vitamins as antioxidants capable of preventing the onset of cardiomyopathy in humans appears to require further investigation but may significantly reduce the incidence of this condition in the future.